Adultery Criminalization Spirit in Islamic Criminal Law: Alternatives in Indonesia’s Positive Legal System Reform - Supardin, Supardin; Syatar, Abdul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
This study aims to provide new ideas in the criminal law reform discourse in Indonesia, especially concerning the adultery issue, by employing a socio-legal approach and Islamic criminal law. The socio-legal approach was performed by combining normative analysis and non-legal scientific tactics in observing the applicable law. Meanwhile, the Islamic criminal law was used to assess and contribute new ideas to the Indonesian legal system in the future, presuming criminal law reforms are implemented. The results indicated fundamental weaknesses in Article 284 of the Criminal Code (KUHP) in terms of defining adultery and the prescribed sanctions. Hence, the community’s need for efforts to reform the adultery penalty following the national culture is inevitable. The best solution is that the spirit of adultery sanctions in Islamic criminal is expected to be an alternative to renew Indonesia’s criminal law system in the future. Although some elements of the nation may not expect the form of adultery sanction in Islamic penalties, the spirit in it aims to have strong legal certainty and maintain human life